2002
DOI: 10.1111/1468-2397.00215
|View full text |Cite
|
Sign up to set email alerts
|

Coping with long–term unemployment: economic security, labour market integration and well–being. Results from a Danish panel study, 1994–1999

Abstract: On the basis of a Danish panel study of the long–term unemployed 1994–1999, the article challenges core premises underlying labour market reforms, assigning too high a priority to work and work incentives, and too little priority to social protection. Economic hardship has become widespread among long–term unemployed even in Denmark, and this is a more serious threat against well–being than unemployment as such. Generous social security, denounced as ‘passive support’, enables the unemployed to cope with their… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
37
0
4

Year Published

2007
2007
2017
2017

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(42 citation statements)
references
References 6 publications
1
37
0
4
Order By: Relevance
“…Some argue that workfare volunteering disempowers people by depicting them as passive citizens, making them feel dependent and controlled (Andersen 2002), at the expense of their own sense of agency (Bessant 2000;Owen 1996) and autonomy (Warburton and Smith 2003). This is mainly due to the requirement (Levy 2006), but also to the lack of freedom of choice (Warburton and Smith 2003) and voice (Knijn and van Berkel 2003).…”
Section: Outcomes Of Workfare Volunteeringmentioning
confidence: 99%
See 1 more Smart Citation
“…Some argue that workfare volunteering disempowers people by depicting them as passive citizens, making them feel dependent and controlled (Andersen 2002), at the expense of their own sense of agency (Bessant 2000;Owen 1996) and autonomy (Warburton and Smith 2003). This is mainly due to the requirement (Levy 2006), but also to the lack of freedom of choice (Warburton and Smith 2003) and voice (Knijn and van Berkel 2003).…”
Section: Outcomes Of Workfare Volunteeringmentioning
confidence: 99%
“…Based on these studies, we would expect (workfare) volunteering to be a promising way of improving the labor market prospects of Turkish, Moroccan and Surinamese women in the Netherlands. However, studies on workfare volunteering found that it also results in various negative outcomes that may affect labor market opportunities, such as feelings of disempowerment (Marston 2005), a loss of a sense of agency (Bessant 2000;Owen 1996) and feeling dependent (Andersen 2002).…”
mentioning
confidence: 99%
“…From this perspective, unemployment‐related allowances first of all provide financial resources and hence create incentives to continue active job search (see e.g., Addison & Portugal, ; Rosholm & Vejlin, ). Secondly, providing financial resources to the unemployed may also indirectly improve their personal resources by partly preventing the decline in psychological well‐being observed during unemployment (Ervasti & Venetoklis, ; Fryer, ; Goul Andersen, ; Leana & Feldman, ; Nordenmark Strandh, & Layte, ; Whelan, ). This is crucial, as we know that psychological well‐being is an important determinant for job search behaviour and subsequent employment outcomes (Meyers & Houssemand, ).…”
Section: Host Country Characteristics and Immigrant Unemploymentmentioning
confidence: 99%
“…The unemployed try to find various ways of coping with the transition from employment to unemployment (Halvorsen, 1999). The extent to which they succeed depends on an array of personal, social and economic resources, of which, in the light of recent evidence (Halvorsen, 1999;Nordenmark and Strandh, 1999;Julkunen, 2001;Goul Andersen, 2002;Alvaro and Garrido, 2003), economic resources are the most crucial.…”
Section: Introductionmentioning
confidence: 99%